The Contribution of Family-Centered Services to Enhanced Quality of Life and Reduced Distress in Families of Children With Disabilities During the COVID-19 Pandemic - Ayelet Gur
This study examines family distress and quality of life among families of children with disabilities during the first wave of the COVID-19 pandemic in Israel. It considers the role of family resources, a sense of community, and the services provided by the Israeli family-centered program (IFCP). One hundred eighty-two parents of children with disabilities participated in this study through an online survey. Structural equation modeling showed that extensive family resources, better operation of the IFCP, and a sense of community were associated with a better quality of life. Lack of family resources was associated with family distress. A regression-based path analysis indicated that this association was moderated by components of the IFCP. Family-centered services were associated with a family$1 (Bs quality of life and experience of distress in times of national crisis. The results highlight the importance of the partnership between parents of children with disabilities and service providers.s